2020
DOI: 10.3390/agronomy10040542
|View full text |Cite
|
Sign up to set email alerts
|

Forage Performance and Detection of Marker Trait Associations with Potential for Napier Grass (Cenchrus purpureus) Improvement

Abstract: The evaluation of forage crops for adaptability and performance across production systems and environments is one of the main strategies used to improve forage production. To enhance the genetic resource base and identify traits responsible for increased feed potential of Napier grass, forty-five genotypes from Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), Brazil, were evaluated for forage biomass yield and feed nutritional quality in a replicated trial under wet and dry season conditions in Ethiopia.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 38 publications
4
24
0
1
Order By: Relevance
“…Similarly, thirteen markers were detected for ADF, NDF and ADL, which are mainly linked with the cell wall components of fibre and lignin that negatively affect the feed nutritional quality. Improving the digestibility of forages by reducing lignin and fibre is a major goal in forage crop breeding programs (Habte et al, 2020; Rocha et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, thirteen markers were detected for ADF, NDF and ADL, which are mainly linked with the cell wall components of fibre and lignin that negatively affect the feed nutritional quality. Improving the digestibility of forages by reducing lignin and fibre is a major goal in forage crop breeding programs (Habte et al, 2020; Rocha et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 12 harvests were conducted, following every eight weeks of regrowth, in both WS and DS conditions. Data of morphological, agronomic, and feed quality traits were collected from three randomly selected plants per row in each of the three soil moisture conditions, as described in (Habte et al, 2020). The agro-morphological traits collected were plant height (PH) in centimeter (cm), leaf length (LL) in cm, leaf width (LW) in millimeter (mm), stem thickness (ST) in mm, tiller number (TN) count, internode length (IL) in cm, total fresh weight (TFW) in t/ha, total dry weight (TDW) t/ha, leaf-stem-ratio (LSR), and water use efficiency (WUE) in g/l (Dry matter produced per liter of water).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…immigrant established best in March and the Pustinny-Select population established best in May [17]. In contrast, the evaluation of Brazilian Napier grass genotypes in Ethiopia, resulted in substantial differences in forage yield and quality between wet and dry seasons, but also indicated that the genotypes with the greatest forage production were consistent across both seasons [18]. Thus, the effect of genotype × environment interaction on rangeland agriculture is species, genotype, location, and trait dependent.…”
mentioning
confidence: 91%
“…Transcriptomic and proteomic techniques resulted in the identification of a number of candidates for the molecular improvement of alfalfa salinity tolerance [21]. Finally, marker-trait associations in Napier grass identified polymorphisms with potential utility for identifying genotypes with high agronomic performance [18]. Although the potential for marker-assisted and genomic selection is still untapped, these techniques show great promise as the efforts increase and receive more emphasis.…”
mentioning
confidence: 99%